2013
DOI: 10.5301/jva.5000142
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Catheter Thrombi: Visualization and Quantification of Microstructures and Cellular Composition

Abstract: Integration of SEM and TPLSM was found to be an excellent tool for characterizing thrombi in hemodialysis CVC removed from patients. Protocols and techniques presented here may be useful in the development and testing of new strategies for limiting thrombus formation on vascular access because of CVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Blood velocity and pressure fluctuations close to the catheter surface could cause a transition from a laminar to a turbulent flow regime and promote the onset of the blood clotting process with thrombus formation in the catheter holes. Microscopic structure and composition of venous thrombi have been previously reported , and we recently showed that blood thrombi formed in a hemodialysis CVC present a complex structure and are mainly composed of fibrin and erythrocytes . A fibrin sheath commonly develops within 24 h after CVC insertion at the region where the catheter contacts the vessel wall, and may completely enclose the proximal portion of the CVC in 5 to 7 days .…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Blood velocity and pressure fluctuations close to the catheter surface could cause a transition from a laminar to a turbulent flow regime and promote the onset of the blood clotting process with thrombus formation in the catheter holes. Microscopic structure and composition of venous thrombi have been previously reported , and we recently showed that blood thrombi formed in a hemodialysis CVC present a complex structure and are mainly composed of fibrin and erythrocytes . A fibrin sheath commonly develops within 24 h after CVC insertion at the region where the catheter contacts the vessel wall, and may completely enclose the proximal portion of the CVC in 5 to 7 days .…”
mentioning
confidence: 70%
“…The study was approved by the Ethics Committee Concerning Research Involving Human Subjects and Clinical Trials (Process 04/2010) of Trento, Italy. Samples were treated as previously reported . Briefly, CVCs were rinsed in sterile saline and fixed in 4% buffered formaldehyde immediately after removal from the patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enumeration of the two features of interest was performed according to a protocol adapted from Lucas et al . (). A squared grid of 15 μ m element size was superimposed to each acquired image and the observation of each single cross‐point allowed to quantify the occurrence of hyphae or blastospores.…”
Section: Methodsmentioning
confidence: 97%
“…A set of 20 electron-micrographs per each sample was than obtained in the same point of interest at a magnification of 2000x. The composition of the thrombus was determined by performing a semiquantitative analysis of the SEM images, modifying the procedure previously proposed by Lucas et al (Lucas, 2013). Briefly, a squared grid of 10μm element size was superimposed to each SEM image to obtain a total of 400 point of interest per sample.…”
Section: Scanning Electron Microscopy and Compositional Analysismentioning
confidence: 99%